(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
This study examines the potential to tree component biomass, biomass for bioenergy product and sequester carbon of forest area. CO2FIX program was used to determine about these value. In order to know about these values, we used CO2FIX program. Thinning harvesting scenarios were analysed, involving the establishment of short rotation harvesting (each 10 years) and long rotation plantations (200 year). As a result, an overall tree biomass components (stem, foliage, branch and root) were respectively recorded as follow: 2.49 ton/ha±0.67, 0.14 ton/ha±0.03, 0.35 ton/ha±0.09 and 0.65 ton/ha±0.18. The potential of biomass for bioenergy product and sequester carbon was increase until the end of project simulation. The increase average biomass of bioenergy was 25.96 Mg/ha±13.46 and the average of net sequestered carbon increase about 16.6±35.9 MgCO2equiv/ha. Our analysis on this study for all research variables is highest at each 40 years period because at this age, the rate of increment in the biomass of the tree is maximized.